Class Interaction Analysis in English Learning Based On Flanders Interaction Analysis Category System (FIACS) - Danti Novianti; Hijrah; Nunung Anugrawati (English Language Teaching Methodology, 2023)
The objective of this research is to describe the kinds of classroom interaction take place between teacher and student and describes what is the most dominant talk take place in classroom interaction based on the Flanders Class Interaction Analysis Category System (FIACS).This research used descriptive qualitative research. The data of this study are the interaction between teacher and students in the classroom. The data were taken by recording the classroom interaction. The subject of this research was 17 students and one English Teacher. The researcher used observation for techniques of collecting data. Flanders Interaction Analysis used to identify and analyze teacher and students interaction in classroom.Based on the result of this study, it could be concluded there are 10 categories of interaction, 7 categories of teacher talk, such as accepts feelings, praises or encourage, accepts or uses students ideas, asking question, lecturing, giving directions, criticizing or justifying authority; 2 categories of students talk namely students talk response and students talk initiation and 1 category of silence. The researcher concludes that the teacher was dominant in the classroom. It proved by the percentage of teacher talk was 58.70% than students talk was 30.34%, and the kinds of classroom interaction, the students participation was 30.34% has higher percentage than others and silence was 10.94%.